Trinidad Food Producers’ Training Needs for Food Security and Implications for Extension - Grady T. Roberts; Wayne G Ganpat; Lendel Narine; Seth B Heinert; Mary T Rodriguez (Journal of International Agricultural and Extension Education, 2015)
The purpose of this study was to explore farmers’ knowledge of food security issues in Trinidad. Such information can be used to develop appropriate extension training interventions. Using a Borich (1980) methodology, a total of 300 agricultural producers in Trinidad were surveyed with an instrument that consisted of two parts: (a) personal demographic and farm related questions, and (b) indicators of knowledge and importance of 27 food security issues derived from The National Food Production Action Plan 2012 – 2015. Overall, the top five issues identified by producers were: (a) the incentive program that is focused on outputs; (b) research and development for both livestock and crop farmers; (c) partnerships between public sector agencies, research institutions, and the private sector to provide suitable capacity to deliver all food production programs; (d) postharvest technologies that create employment opportunities, increase returns to farmers, improve food quality, and ensure food safety; and (e) and technology packages (of information) to help farmers improve yield, quality, and availability. All 27 food security issues varied in at least one of the categories assessed: 22 issues varied by location; 18 issues varied by farm type; 5 issues varied by farming status; and 19 issues varied by education level of the farmer. These results can guide extension programming in Trinidad and also be informative for policy makers.
Keywords: food security; needs assessment; Caribbean; Trinidad and Tobago; agricultural producers; farmer knowledge